The Guidelines For Internal Communication Management of The Faculty of Veterinary Medicine, Chiang Mai University - chaiprasert, Siriyanee; Mahavīro, Asst. Prof. Dr., Phramaha Sakun (MCU Haripunchai Review, 2026)
This research aimed to: 1) examine the current state of internal organizational communication management at the Faculty of Veterinary Medicine, Chiang Mai University, and 2) identify guidelines for managing internal organizational communication at the Faculty of Veterinary Medicine, Chiang Mai University. This qualitative study included 10 key informants and 6 focus group participants. Research instruments consisted of interview guides and focus group discussion guides. Data were analyzed using content analysis. The findings revealed: 1)Regarding the current state of internal organizational communication management at the Faculty of Veterinary Medicine, Chiang Mai University: To effectively drive communication and create shared understanding of the faculty’s strategic plan, clear communication guidelines and processes need to be established. Internal communication at the faculty requires staff participation. However, there is still a lack of message prioritization, such as distinguishing between urgent news, general announcements, and strategic communications. Sometimes information is disseminated through multiple channels without proper filtering, resulting in redundancy or inaccuracy. 2)Guidelines for managing internal organizational communication at the Faculty of Veterinary Medicine, Chiang Mai University include: (1) clearly defining communication roles and responsibilities to ensure information comes from credible sources, (2) designing messages to be concise, focused, and attractively formatted according to information type, (3) using diverse and appropriate communication channels with established standards for formal channel usage, (4) creating monitoring and evaluation systems using feedback from message recipients for improvement, and (5) promoting two-way communication to foster staff participation and organizational engagement. The SMCR model should be used to clearly define communication roles and responsibilities with credibility, design messages that are concise, focused, and attractively formatted by information type, and utilize diverse and appropriate communication channels.